The The Role of Financial Flexibility: ESG Performance, ROA and Firm Value - Akbar, Imam; Setiana, Sinta (Dinasti Publisher, 2024)
The purpose of this study was to determine and analyze the effect of ESG performance (ESG), ROA, and whether financial flexibility as a moderating or mediating variable on Firm Value. The population in this study are energy and mineral companies listed on the IDX for the period 2018-2022. Purposive sampling method was used to determine the number of samples that met the criteria and resulted in 12 companies as samples in the study. The research data uses secondary data obtained from the company's annual financial report, sustainability report and Thomson Reuter (Refinitiv) report. This study uses several tests, namely classical assumption testing, panel data regression, sobel test and Moderated Regression Analysis (MRA) using Eviews 13 statistical tools. ESG, ROA and Financial Flexibility simultaneously affect firm value with Leverage as control variables. Financial flexibility and ROA do not mediate ESG on Firm Value. Financial flexibility moderates ESG on firm value, but ROA does not moderate on firm value. It is proven that financial flexibility is a moderating variable for the influence of ESG on firm value where the role of the moderating variable of financial flexibility strengthens the influence of ESG on firm value. There are two main findings in the study, namely the role of financial flexibility can strengthen the influence of ESG performance on firm value and the joint role of ESG, ROA and financial flexibility with leverage as a control variable can increase firm value.